Bombesin excites a subpopulation of 5-hydroxytryptamine-sensitive neurones in the rat dorsal raphe nucleus in vitro. - Pinnock, R D (1991)
1. The effects on dorsal raphe neurones of the peptides bombesin, gastrin-releasing peptide and neuromedin B were studied using intracellular recording techniques from slices of rat brain maintained in vitro. The peptides were added to the solutions perfusing the slices. 2. The peptides bombesin, gastrin-releasing peptide and neuromedin B depolarized neurones in the dorsal raphe nucleus. The same neurones were depolarized by phenylephrine and hyperpolarized by 5-hydroxytryptamine (5-HT) but were insensitive to sulphated cholecystokinin octapeptide (CCK). 3. The responses to the peptides were not blocked by CCKA, CCKB and alpha 1-adrenoreceptor antagonists. 4. The response to the peptides persisted in the presence of tetrodotoxin (TTX) and low-calcium, high-magnesium-containing artificial cerebrospinal fluid (ACSF). 5. Under voltage clamp conditions the peptides caused a decrease in membrane conductance accompanied by an inward current. The reversal potential for the event was the same as that for 5-HT. 6. The results of the present study demonstrate that bombesin and the structurally related peptides gastrin-releasing peptide (GRP) and neuromedin B depolarized a subpopulation of raphe 5-HT neurones by acting on a postsynaptically located receptor linked to potassium channels.